Bacteria consortia enhanced hydrocarbon degradation of waxy crude oil - Raja Abd Rahman, Raja Noor Zaliha; Latip, Wahhida; Adlan, Nur Aina; Sabri, Suriana; Mohamad Ali, Mohd Shukuri (Springer Nature, 2022)
Waxy crude oil is a problem to the oil and gas industry because wax deposition in pipelines reduces the quality of the crude oil. Currently, the industry uses chemicals to solve the problem but it is not environmentally friendly. As an alternative, the biodegradation approach is one of the options. Previously eleven thermophilic bacteria were isolated and exhibited high ability to degrade hydrocarbon up to 70% of waxy crude oil. However, despite the successful study on these single bacteria strains, it is believed that biodegradation of paraffin wax requires more than a single species. Five consortia were developed based on the biodegradation efficiency of 11 bacterial strains. Consortium 3 showed the highest biodegradation (77.77%) with more long-chain alkane degraded throughout the incubation compared to other consortia. Enhancement of hydrocarbon degradation was observed for all consortia especially in long chain alkane (C18-C40). Consortium 3 exhibited higher alkane monooxygenase, alcohol dehydrogenase, lipase, and esterase activities. Moreover, the dominant bacteria in the consortia were determined by denaturing gradient gel electrophoresis (DGGE), which showed the domination of genera Geobacillus, Parageobacillus, and Anoxybacillus. It can be concluded that the bacterial consortia showed higher biodegradation and improved degrading more long-chain hydrocarbon compared to a single isolate.